From south central to southside: gang transnationalism, masculinity, and disorganized violence in Belize City - Baird, Adam (Studies in transgression, 2024)
"This book looks at violent gang cultures in Belize City, arguing that hegemonic masculinities imported from American gang cultures through deportation and popular media evolved in a context of postcolonial extreme poverty and disorganized urban life to drive a deadly culture of gendered violence"--